SOCIAL AND CULTURAL PROBLEMS IN ISLAMIC BOARDING SCHOOL; COMPARATIVE STUDY IN FIVE BOARDING SCHOOL IN JAVA-SUMATRA - Restu Tria Anugrah; Rahma Vitranti; Shonia Ummu Khabibah; Ihda Fatrisia; Karni Karni; Salma Putri Adani; Didi Pramono (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
Pesantren is a place to study which is more important education and learning based on religious knowledge. Generations of graduates from Islamic boarding schools are expected to be able to develop and practice knowledge in society in accordance with religious values. Islamic boarding schools that are established in Indonesia certainly have differences, both from the history, learning methods, facilities, problems, and even culture. This study aims to find out the problems and culture in Islamic boarding schools, especially Islamic boarding schools located in Pekalongan , Wonosobo, Banjarnegara, Karawang, and also North Bengkulu. As for the descriptive method with a comparative approach is the method used, which is useful in comparing a phenomenon, event, and also the symptoms that occur. The benefits that can be obtained from the results of conducting this research are that it can provide an overview of the problems are culture that exist in Islamic boarding schools. The results obtained are the similarity of problems such as truancy, ilness, and lack of educator. The differences are the type of pesantren, history, and also complementary facilities. In addition, cleaning the environment has become a culture that is carried out in the five pesantren. The conclusion in this study is that in dealing with problems that arise, the need for cooperation between pesantren residents and mutual support for each other. The differences are the type of pesantren, history, and also complementary facilities. In addition, cleaning the environment has become a culture that is carried out in the five pesantren. The conclusion in this study is that in dealing with problems that arise, the need for cooperation between pesantren residents and mutual support for each other. The differences are the type of pesantren, history, and also complementary facilities. In addition, cleaning the environment has become a culture that is carried out in the five pesantren. The conclusion in this study is that in dealing with problems that arise, the need for cooperation between pesantren residents and mutual support for each other.